Geographies of Theatre: the Finnish National Theatre in Stockholm in 1956 - Korsberg, Hanna (Nordic Theatre Studies, 2016)
During the Cold War, the Finnish National Theatre actively sought possibilities for international visits and co-operation. It wanted to showcase its work abroad and especially connect itself with Western European theatres. In 1956, the Finnish National Theatre visited Stockholm. In terms of politics, it was interesting that the Finnish National Theatre chose to perform Aleksis Kivi’s The Seven Brothers and especially interesting that it performed Anton Chekhov’s The Three Sisters. It seems to be the case that there was a national border between the Finnish National Theatre and Anton Chekhov’s play that was hard to cross. The director of the production, Eino Kalima, was described as an expert in interpreting Chekhov due to his background as a student of Stanislavski. This was a myth created by the director of the Finnish National Theatre. However, it increased international interest for the production of The Three Sisters with Kalima as its director. Furthermore, it supported the theatre’s attempts at seeking mobility and engaging in international, cultural encounters.